(untitled) (Research, Society and Development, 2022)
Patients admitted to the Intensive Care Unit (ICU) have a prevalence of malnutrition higher than 35% at the time of admission, and even critically ill patients with a nutritional diagnosis of eutrophy, after hospital admission, can quickly develop protein-calorie malnutrition. Given the changes and unforeseen events that occur in the ICU with the patient, influencing the decrease in caloric-protein supply and the correct administration of the enteral diet in the ICU, as well as the need to reduce costs and waste, the objective of this research is to evaluate caloric-protein adequacy between closed system Enteral Nutrition Therapy (ENT) prescribed and administered/infused in critically ill patients admitted to an ICU and to verify the main reasons for wastage of enteral diets. This is a longitudinal, observational, and descriptive research, carried out at the University Hospital, in the city of Lagarto (HUL), for 30 days during the year 2021. Data collection was carried out in the ICU, which was selected for presenting the largest number of patients using closed system ENT, targeting adults and elderly in critical condition. Most patients were hospitalized for infectious diseases (29.4%), and the main reason for the indication of ENT was neurological reasons (64.7%). Regarding the nutritional profile of patients, it was observed that 52.9% were underweight. Among the reasons for the wastage of enteral diets, hemodynamic instability, and infusion pump error were cited, but for the most part, professionals had no information about the cause.